Paleoenvironments and Sequence Development of the Miocene succession , Western and Southern Iraq - D. Gayara, Ali; K. Ajar, Dhyaaldain (Iraqi Journal of Science, 2023)
The Miocene succession of western and southern Iraq is represented by theEuphrates, Ghar, Jeribe, Nfayil, Fatha, and Injana formations. The EuphratesFormation (Early Miocene) consists mainly of shallow marine facies; it`s equivalentthe Ghar Formation (Early- Early Middle Miocene) is represented by continentalclastic facies. The Jeribe Formation (Early Middle Miocene) represents shallowmarine environment. The Nfayil Formation (Middle Miocene) also of shallow marineenvironment, it`s equivalent the Fatha Formation is represented mainly by supratidalmarine environment. The Injana Formation (Late Miocene) represents the clasticcontinental facies.The studied succession was highly affected by many diagenetic processes such asdolomitization, dedolomitization, dissolution and cementation with less effectivemicritization, neomorphism, and compaction.Four third order cycles were recognized in the studied sections, These include:cycle A of the Miocene Euphrates Formation and it`s equivalent the lower part of theGhar Formation, cycle B of the Early Middle Miocene Jeribe Formation and it'sequivalent the upper part of the Ghar Formation, cycle C of the Middle MioceneNfayil Formation and it`s equivalent the Fatha Formation, and cycle D of the LateMiocene Injana Formation. Each third order cycle can be subdivided into a number offourth order cycles. All of the fourth order cycles are assymmetrical reflecting animbalance between the relative sea level and carbonate production. A variationbetween the different sections in nature of cyclic deposition reflects the difference oflocal tectonic effect on the sequence development.